2002
DOI: 10.1046/j.1365-2591.2002.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Periapical lesions accidentally filled with calcium hydroxide

Abstract: Extensive extrusion of calcium hydroxide into the periapical tissues does not appear to comprise periapical healing. Despite this finding, the deliberate extrusion of dental materials into the apical tissues is not advocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 16 publications
1
35
0
Order By: Relevance
“…It could be noticed that the CHG was always one experimental period behind the IG and this group was one experimental period behind the control wound, which means that repair in the IG was faster than in the CHG. The results found for the quantitative analysis could relate the histological and clinical findings (10,12,13,15,18). The presence of inflammatory cells (macrophages, lymphocytes and neutrophils) was higher in the control wound after three days and similar after five days.…”
Section: • 3 Daysmentioning
confidence: 72%
See 1 more Smart Citation
“…It could be noticed that the CHG was always one experimental period behind the IG and this group was one experimental period behind the control wound, which means that repair in the IG was faster than in the CHG. The results found for the quantitative analysis could relate the histological and clinical findings (10,12,13,15,18). The presence of inflammatory cells (macrophages, lymphocytes and neutrophils) was higher in the control wound after three days and similar after five days.…”
Section: • 3 Daysmentioning
confidence: 72%
“…On the other hand, iodoform shows a slow and continuous release of iodine, and an interaction with bacteria, which leads to the stimulation of the inflammatory reaction because of its antigenicity, i.e., iodoform acts as a foreign body and develops an immunological reaction (11,12). So iodoform showed higher efficiency with an inevitable, but shorter delay in the repair, according to clinical findings (10,18). Clinically, the type of lesion and consequently its physical characteristics should be considered to confirm these results.…”
Section: Discussionmentioning
confidence: 99%
“…As 100 ml of water can dissolve only 0.02 g of BaSO 4 it has been proposed to use resorbable iodine compounds like diatrizoate or iothalamate instead of BaSO 4 due to the fact that these do not have a significant effect on the length of the healing period [12]. In a study conducted on the effect of accidental and voluminous Ca(OH) 2 overextrusion into periradicular lesions and tissues on the prognosis of periapical healing by De Moor and De Witte [14] reported that in cases of extensive Ca(OH) 2 overextrusion, repair took more than six months and observed that complete resorption of the paste including BaSO 4 did not occur, eventhough the periradicular radiolucency disappeared. The time taken for periradicular radiolucency to disappear was approximately 24 months in the presented case which is in line with the findings of other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…When calcium hydroxide paste is used as a root canal medication, the anticipated effects include long-acting antimicrobial activity, analgesia, hemostasis, exudate control, cleansing of the root canal wall, and the induction of hard tissue 7,12) . However, the effects on soft tissue have not been clarified 5) . Calcipex ® is strongly alkaline, with a pH of 12.4, and chemical burns of the mucosa have been reported 3,4,14,15) .…”
Section: Discussionmentioning
confidence: 99%